2011
DOI: 10.1179/2042618611y.0000000003
|View full text |Cite
|
Sign up to set email alerts
|

The neurophysiological effects of a single session of spinal joint mobilization: does the effect last?

Abstract: Studies detailing the neurophysiological effects of spinal manual therapy have fueled a paradigm shift away from a strict biomechanical model. However, a recent systematic review of the temporal nature of a single session of spinal thrust manipulation found that the neurophysiological effects were only temporary. The objective of this review was to examine the temporal nature of neurophysiological effects after one session of spinal mobilization. Studies eligible for this review had to report on the temporal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 30 publications
2
40
1
3
Order By: Relevance
“…Decreases heart rate variability [52], salivary amylase [53] and salivary cortisol and insulin levels [52] are also noted after MT. These changes are similar to those observed in animals upon the artificial stimulation of higher centers responsible for descending pain modulation such as the PGA or RVM [54]. Additionally, hypoalgesia through the application of MT is obtained both locally and remotely from the site of application of the stimulus [35] and the duration of the hypoalgesia achieved with MT may last up to 24 h [54].…”
Section: • Neurophysiological Mediatorssupporting
confidence: 56%
“…Decreases heart rate variability [52], salivary amylase [53] and salivary cortisol and insulin levels [52] are also noted after MT. These changes are similar to those observed in animals upon the artificial stimulation of higher centers responsible for descending pain modulation such as the PGA or RVM [54]. Additionally, hypoalgesia through the application of MT is obtained both locally and remotely from the site of application of the stimulus [35] and the duration of the hypoalgesia achieved with MT may last up to 24 h [54].…”
Section: • Neurophysiological Mediatorssupporting
confidence: 56%
“…This study did not aim to investigate long-term responses, as a recent systematic review has reported that the neurophysiological effects of a single manipulation may not exceed 5 minutes in duration. 25 Nevertheless, despite the limitations of the study, the results should cultivate additional inquiry into the theories concerning the supraspinal mechanisms associated with manipulation and how such mechanisms may contribute to successful outcomes in specific patient populations.…”
Section: Limitationsmentioning
confidence: 99%
“…14 In addition, a third systematic review that included both randomized and non-randomized controlled trials concluded that a single session of spinal mobilization may have little or no clinically meaningful or lasting effect. 15 The study by…”
Section: Introductionmentioning
confidence: 99%